At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the given equation [tex]\(\frac{(1+\tan x)^2}{\sec x} = \sec x + 2 \sin x\)[/tex], we will simplify both sides using trigonometric identities.
### Step 1: Simplify the left-hand side (LHS)
We begin with:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} \][/tex]
First, recall the trigonometric identities:
[tex]\[ \tan x = \frac{\sin x}{\cos x} \][/tex]
[tex]\[ \sec x = \frac{1}{\cos x} \][/tex]
Using these identities, we can rewrite [tex]\(1 + \tan x\)[/tex] as:
[tex]\[ 1 + \tan x = 1 + \frac{\sin x}{\cos x} = \frac{\cos x + \sin x}{\cos x} \][/tex]
Then, square it:
[tex]\[ (1 + \tan x)^2 = \left( \frac{\cos x + \sin x}{\cos x} \right)^2 = \frac{(\cos x + \sin x)^2}{\cos^2 x} \][/tex]
Now, dividing by [tex]\(\sec x\)[/tex]:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \frac{(\cos x + \sin x)^2}{\cos^2 x} \cdot \cos x = \frac{(\cos x + \sin x)^2}{\cos x} \][/tex]
### Step 2: Expand and simplify
Expand [tex]\((\cos x + \sin x)^2\)[/tex]:
[tex]\[ (\cos x + \sin x)^2 = \cos^2 x + 2 \cos x \sin x + \sin^2 x \][/tex]
Using the Pythagorean identity [tex]\(\cos^2 x + \sin^2 x = 1\)[/tex], we have:
[tex]\[ \cos^2 x + \sin^2 x = 1 \][/tex]
Substitute back into our expression:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \frac{1 + 2 \cos x \sin x}{\cos x} \][/tex]
### Step 3: Simplify further
Note that:
[tex]\[ 2 \cos x \sin x = \sin(2x) \][/tex]
However, it may not directly help us here. Instead, we proceed by simply substituting and separating terms in the numerator:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \frac{1}{\cos x} + \frac{2 \cos x \sin x}{\cos x} \][/tex]
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \sec x + 2 \sin x \][/tex]
### Step 4: Compare with the right-hand side (RHS)
We already have:
[tex]\[ \sec x + 2 \sin x \][/tex]
So our simplified LHS becomes:
[tex]\[ \sec x + 2 \sin x \][/tex]
Which exactly matches the RHS:
[tex]\[ \sec x + 2 \sin x \][/tex]
Thus, we have verified that:
[tex]\[ \frac{(1+\tan x)^2}{\sec x} = \sec x + 2 \sin x \][/tex]
Hence, the given equation is an identity and is satisfied for all [tex]\(x\)[/tex] where the trigonometric functions are defined.
### Step 1: Simplify the left-hand side (LHS)
We begin with:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} \][/tex]
First, recall the trigonometric identities:
[tex]\[ \tan x = \frac{\sin x}{\cos x} \][/tex]
[tex]\[ \sec x = \frac{1}{\cos x} \][/tex]
Using these identities, we can rewrite [tex]\(1 + \tan x\)[/tex] as:
[tex]\[ 1 + \tan x = 1 + \frac{\sin x}{\cos x} = \frac{\cos x + \sin x}{\cos x} \][/tex]
Then, square it:
[tex]\[ (1 + \tan x)^2 = \left( \frac{\cos x + \sin x}{\cos x} \right)^2 = \frac{(\cos x + \sin x)^2}{\cos^2 x} \][/tex]
Now, dividing by [tex]\(\sec x\)[/tex]:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \frac{(\cos x + \sin x)^2}{\cos^2 x} \cdot \cos x = \frac{(\cos x + \sin x)^2}{\cos x} \][/tex]
### Step 2: Expand and simplify
Expand [tex]\((\cos x + \sin x)^2\)[/tex]:
[tex]\[ (\cos x + \sin x)^2 = \cos^2 x + 2 \cos x \sin x + \sin^2 x \][/tex]
Using the Pythagorean identity [tex]\(\cos^2 x + \sin^2 x = 1\)[/tex], we have:
[tex]\[ \cos^2 x + \sin^2 x = 1 \][/tex]
Substitute back into our expression:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \frac{1 + 2 \cos x \sin x}{\cos x} \][/tex]
### Step 3: Simplify further
Note that:
[tex]\[ 2 \cos x \sin x = \sin(2x) \][/tex]
However, it may not directly help us here. Instead, we proceed by simply substituting and separating terms in the numerator:
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \frac{1}{\cos x} + \frac{2 \cos x \sin x}{\cos x} \][/tex]
[tex]\[ \frac{(1 + \tan x)^2}{\sec x} = \sec x + 2 \sin x \][/tex]
### Step 4: Compare with the right-hand side (RHS)
We already have:
[tex]\[ \sec x + 2 \sin x \][/tex]
So our simplified LHS becomes:
[tex]\[ \sec x + 2 \sin x \][/tex]
Which exactly matches the RHS:
[tex]\[ \sec x + 2 \sin x \][/tex]
Thus, we have verified that:
[tex]\[ \frac{(1+\tan x)^2}{\sec x} = \sec x + 2 \sin x \][/tex]
Hence, the given equation is an identity and is satisfied for all [tex]\(x\)[/tex] where the trigonometric functions are defined.
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.